METHODS OF ESTIMATING COSTS EFFICIENCY IN THE AGRICULTURAL COMMERCIAL COMPANIES IN ROMANIA - Stoicea, Paula; Dinu Toma, Adrian; Stoian, Elena (Economics of Agriculture, 2011)
Production cost and a large spectre of indicators needed for farm decision making process may easily be determined through the use of direct-costing method. This method uses only variable costs for the agricultural product cost calculation, given that the fxed expenses influence directly the gross fnancial result of the farm. The study was performed based on the data collected in the agricultural year of 2010, from a vegetable farm from the region of South-Muntenia, Romania, having a surface of 15 ha, consecutively cultivating early potato and autumn cabbage. This computation method brings the advantage of emphasizing the most proftable cultivated agricultural products, ensuring a strict control over expenses, by simplifed calculation, even though diffculties may appear when separating the variable expenses from the fxed ones. The indicators calculated for the studied farm have shown crop proftability, lack of risks and farm capacity to adapt in due time and with minimum effort to the changes brought about by the conditions generated by the social-economic environment.